Developing Islamic Family Resilience Teaching Materials to Enhance Marital Readiness for High School Students - Ayu, Sovia Mas; Junaidah, Junaidah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study focuses on the development of teaching materials on Islamic family resilience as part of the Islamic Religious Education (PAI) curriculum to prepare high school students for future marital life. These materials emphasize five dimensions of family resilience: religious, physical, psychological, economic, and social. The research involved expert validation, teacher feedback, and student testing to ensure the quality and effectiveness of the materials. Results showed high levels of content validity (91.7%), language clarity (75%), and presentation quality (83%), with user responses reaching 92%. These outcomes indicate the materials' effectiveness in enhancing students' understanding of family resilience and preparing them for the responsibilities of marriage. The study underscores the importance of integrating Islamic values into educational resources to address societal challenges such as early divorce and domestic violence. While the research is limited to a specific region and subject, it provides valuable insights into curriculum innovation and the role of education in fostering resilient and harmonious family units. Further research is recommended to explore the broader application of such materials in diverse educational and cultural contexts.